Extensão rural no Brasil: uma análise da instrumentação da ação pública - Pacífico, Daniela Aparecida (2022)
This article aims to analyze instruments, techniques and tools of public action in Brazil with a focus on the performance of technical assistance and governmental and non-governmental rural extension, from 2010 to 2020. The work analyzed the mechanisms of operation of public action, evidencing them from the relationships they were able to organize, and the implications during the implementation of the Brasil Sem Miséria Rural Plan (BSM-Rural). The hypothesis is that the governmental and non-governmental rural extension, when operating instruments, techniques and tools designed to implement the BSM-Rural, contributed to the creation of the techniques and tools for the operationalization of the ATER Law, in an orchestrated overlapping of instruments. and producing effects. From a methodological point of view, documental research, a bibliographic review of specialized literature, and field research carried out in 2013/2015 and 2020/2021 were used. The study was based on HALPERN's public action instrumentation literature; LASCOUMES; LE GALÈS (2014). The work made it possible to understand the movement of the instruments of public action, the relationships and the effects generated in the convergence of public policies to face rural poverty in Brazil and, above all, the origin of the techniques and tools that operated the ATER.